2007
DOI: 10.1002/dc.20627
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the ThinPrep® imaging system in a high‐volume metropolitan laboratory

Abstract: The Papanicolaou test has proven to be the most effective cancer screening test ever developed. However, with a declining number of skilled cytotechnologists, there is an increased need for computer assistance in cervical cancer screening. The ThinPrep Imaging System (Cytyc Corporation, Marlborough, MA) is a unique system that combines computer imaging technology and human interpretive expertise in the review of ThinPrep Pap test slides. The purpose of this study is to report on the introduction and validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 7 publications
8
93
2
2
Order By: Relevance
“…9 Dziura et al and Miller et al also described a significant increase in the detection of histologically proven HSIL in both the atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (ASC-H) and HSIL cytology categories in their practice. 10,11 An increased accuracy in the detection of HSIL was also reported by Chivukula et al with the use of TIS. 12 Davey et al reported that the TIS detected 1.29 more cases of histologic HSIL per 1000 women screened than conventional cytology.…”
Section: Discussionmentioning
confidence: 58%
“…9 Dziura et al and Miller et al also described a significant increase in the detection of histologically proven HSIL in both the atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (ASC-H) and HSIL cytology categories in their practice. 10,11 An increased accuracy in the detection of HSIL was also reported by Chivukula et al with the use of TIS. 12 Davey et al reported that the TIS detected 1.29 more cases of histologic HSIL per 1000 women screened than conventional cytology.…”
Section: Discussionmentioning
confidence: 58%
“…6 As stated in Chapter 1 and shown in Table 1, previous studies comparing automated with manual reading have tended to indicate higher rates of cytological abnormality and some have found increased rates of CIN2+. Some of these studies 23,27 have been performed simply comparing cytological abnormality rates in consecutive periods of time, and others have used a split sample design, 16,24,26 whereby the same sample has been split between a conventional or LBC slide which is manually read and a slide which is subjected to automated reading. Many studies do not use histology as an outcome.…”
Section: Discordant Resultsmentioning
confidence: 99%
“…In the manual-only arm the FMR is by definition equivalent to the MR. Comparison between manual and automated readings in the paired arm The effect of checking on serial readings is shown in Tables [20][21][22][23][24][25][26]. When the MR1 was compared with the FMR, a large proportion of low grades (29.5%) were downgraded to negative.…”
Section: Comparison Between Manual Readings In Manual-only Armmentioning
confidence: 99%
“…Previous data in nonrandomized settings have shown better performance of CAS compared with manually read LBC [16][17][18]28,29 and CC. 15,17 In a large prospective Australian 1 Conventional cytology: total n cytologically positives: 93 (60 histologically confirmed, 33 imputed).…”
Section: Discussionmentioning
confidence: 99%